Carbon footprint of tuna and tuna like production landed based at Bitung fish port - Rahmadi, P; Widodo, A A; Marzuki, R (IOP conference series. Earth and environmental science, 2021)
It is well known that greenhouse gas effects are one of the main factors driving global warming. Substances that play a role in this phenomenon include Carbon dioxide (CO 2 ), Methane (CH 4 ) and Nitrous oxide (N 2 O) which is commonly called as Carbon Substances. The higher the levels of these substances in the air, the greater and faster impact of the greenhouse phenomenon can cause. The current status of global warming has encouraged us to make efforts to reduce and mitigate climate change. Calculation of the addition of carbon substances (Carbon Footprint Inventory - CFI) is the first step in an effort to deal with climate change. It is therefore, as one form of participation in the mitigation of global warming, the calculation of carbon production (carbon footprint) in Tunas (Tuna, Mackerel Tuna and Skipjack) fisheries has been done. The research was subject to Tunas production captured using Pole and Line and landed at Bitung fisheries port. This research utilized primary data collected by field survey, questionnaire, expert adjustment, and secondary data from various data sources both online and offline. The number of respondents were 16 fleets of Pole and Line based in Bitung fisheries port, including its captains, engine master and fishing master in each fleet. Several companies such as ice factories, processing and fuel dealers were also subjected as respondents. Flow charts and Life Cycle Analysis (LCA) are used to map the needs and availability of data which are then applied to CFI based on ISO / TS 14067. CFI ISO/TS 14067 internationally has been published specifically to calculate the CFI of products. The result shows CFI of Tunas product in Bitung was 1.41 ± 0.80 kgCO 2 /kg of Tuna. This number is considered low compared to the CFI tuna fisheries on an international scale reported by the environmental working group - Americans for Prosperity (AFP) which is about 6.1 kg CO 2 /kg of fish. Unfortunately the report from AFP was stated in the general without recognizing the fishing gear whereas in this research it had only calculated the CFI on Pole and Line fisheries.